Mortgages & Mentoring: My Career with Judge Barry S. Schermer - Cynthia Kern Woolverton (Washington University Journal of Law & Policy, 2017)
This Article reflects on the lessons learned and taught by one of Judge Barry Schermer’s co-teachers. Woolverton focuses on teaching the fundamentals of Chapter 13 bankruptcy, including confirming a plan, secured claims, and interest charged, and, along with Judge Schermer, has students apply these complicated concepts to hypothetical situations. The Author recognizes Judge Schermer’s ability to break down these topics in a way that makes them more understandable to a new generation of students and practitioners.
Keywords: Judge Schermer; Mentorship; Washington University School of Law; Chapter 13 Bankruptcy; Bankruptcy Plan; Bankruptcy Code; Mortgages; Real Estate; Mortgage Loans; Securitization; Mortgage-Backed Securities